Antibiotic treatment in pneumonia due to Q fever. Issue 4 (April 1992) - Sobradillo, V; Zalacain, R; Capelastegui, A; Uresandi, F; Corral, J
Abstract : BACKGROUND: Whether Q fever responds better to doxycycline or erythromycin is unknown. METHODS: The efficacy of doxycycline and erythromycin in the treatment of pneumonia due to Q fever was assessed in a prospective, randomised, double blind study of 82 patients with a diagnosis of pneumonia and features suggestive of Q fever infection; 48 proved to have Q fever. Of the 48, 23 received doxycycline 100 mg twice a day and 25 patients received erythromycin 500 mg six hourly, both for 10 days. RESULTS: Both treatment groups had similar demographic characteristics. Fever showed a more rapid reduction in the doxycycline group (3(1.6) days versus 4.3(2) days). Side effects were observed in two patients receiving doxycycline compared with 11 patients receiving erythromycin (p less than 0.01). No differences were observed in other clinical or radiological measures. By day 40 the chest radiograph was normal in 47 of 48 patients. CONCLUSION: The results demonstrate the self limiting and benign nature of most cases of pneumonia due to Q fever. Doxycycline was more effective than erythromycin.